Arrangement of functioning of shadow banking in Poland and in the European Union - Huterska, Agnieszka; Huterski, Robert (Copernican Journal of Finance & Accounting, 2013)
Threats related to improper regulation of shadow banking institutions apply as well to their customers as to whole financial system. It is perceived by financial authorities in Poland (Polish Financial Supervision Authority, the National Bank of Poland), and in the European Union (European Commission, European Central Bank), and also globally (Financial Stability Board). However, the task of proper regulation of shadow banking activities is already in early stage of completion and still requires from institutions mentioned above a lot of work to do.